Dua Fasad Bani Israel: Analisis Komparatif Tafsir Klasik dan Kontemporer atas Al-Isra’ 4–7 - Muqoddam Cholil (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
Surah Al-Isra’ verses 4–7 articulate a divine decree concerning two instances of corruption (fasādain) committed by the Children of Israel, which has generated interpretive divergence within the tradition of Qur’anic exegesis, particularly regarding the identification of the second corruption and its historical scope. This study aims to analyze and compare the interpretations of classical and contemporary Qur’anic exegetes in order to examine differences in interpretive horizons, methodological approaches, and contextual relevance. Employing a qualitative library-based research design, this study applies a comparative tafsir method informed by a contextual hermeneutical framework. Primary sources include classical exegesis Jāmi’ al-Bayān by al-Ṭabari and Tafsīr al-Qur’ān al-‘Aẓīm by Ibn Kathir—as well as contemporary exegesis, namely Fī Ẓilāl al-Qur’ān by Sayyid Qutb and Tafsīr al-Sya‘rāwī by Muhammad Mutawalli al-Sya‘rāwī. The findings indicate that classical exegetes predominantly interpret the two instances of corruption as historical events that occurred prior to the mission of the Prophet Muhammad (peace be upon him), relying heavily on transmitted reports and retrospective historical reconstruction. In contrast, contemporary exegetes adopt a contextual reading that relates the notion of the second corruption to post-prophetic socio-political realities, while remaining grounded in the linguistic structure of the text and the Qur’anic concept of sunnat Allāh in history. This study demonstrates a paradigmatic shift in Qur’anic interpretation from a primarily historical-narrative approach toward a contextual-hermeneutical framework, highlighting the dynamic interaction between text, history, and modern reality in Qur’anic exegesis.